Aspiration pneumonia and pneumonitis: a spectrum of infectious/noninfectious diseases affecting the lung. Issue 2 (April 2019) - Neill, Sarah; Dean, Nathan
Abstract : Purpose of review: Our purpose is to describe aspiration pneumonia/pneumonitis as a spectrum of infectious/noninfectious diseases affecting the lung. We summarize diagnosis, risk factors, treatment, and strategies for prevention of aspiration. Recent findings: Aspiration is present in normal individuals, and disease manifestation depends on the chemical characteristics, frequency, and volume of inoculum. Anaerobes, though present, are no longer the predominant microbes isolated in aspiration pneumonia. Targets for preventing aspiration including improved oral hygiene and positional feeding have had mixed results. Patients diagnosed by clinicians with aspiration pneumonia experience greater morbidity and mortality than patients with community-acquired pneumonia. Summary: Aspiration pneumonia and pneumonitis are part of the pneumonia continuum and share similarities in pathophysiology, microbiology, and treatment. Modern microbiology demonstrates that the lung is not sterile, and isolates in aspiration pneumonia frequently include aerobes or mixed cultures. Treatment for aspiration pneumonia should include antibiotic coverage for oral anaerobes, aerobes associated with community-acquired pneumonia, and resistant organisms depending on appropriate clinical context. Additional studies targeting prevention of aspiration and investigating the increased morbidity and mortality associated with aspiration pneumonia are warranted.